2017
DOI: 10.1007/s10914-017-9405-x
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Ecology in Oligocene Mylodontoid Sloths (Mammalia, Xenarthra) as Revealed by Orthodentine Microwear Analysis

Abstract: Recently, dental microwear analysis has been successfully employed to xenarthran teeth. Here, we present new data on use wear features on 16 molariforms of Orophodon hapaloides and Octodontotherium grande. These taxa count among the earliest sloths and are known from the Deseadan SALMA (late Oligocene). Modern phylogenetic analyses classify Octodontotherium and Orophodon within Mylodontoidea with whom they share lobate cheek teeth with an outer layer of cementum and a thick layer of orthodentine. Similar targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 36 publications
(67 reference statements)
1
8
0
Order By: Relevance
“…The described Mf1 (Fig. 4) shows the same peculiar structure as in other Deseadan Mylodontidae (Kalthoff 2011; Shockey & Anaya 2011; Kalthoff & Green 2018), with a thin peripheral wall of cementum, a thick orthodentine layer, and an extremely reduced central core of vasodentine. Instead, Neogene and Quaternary sloths exhibit a central nucleus of vasodentine (Kalthoff 2011).…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…The described Mf1 (Fig. 4) shows the same peculiar structure as in other Deseadan Mylodontidae (Kalthoff 2011; Shockey & Anaya 2011; Kalthoff & Green 2018), with a thin peripheral wall of cementum, a thick orthodentine layer, and an extremely reduced central core of vasodentine. Instead, Neogene and Quaternary sloths exhibit a central nucleus of vasodentine (Kalthoff 2011).…”
Section: Discussionsupporting
confidence: 53%
“…Concerning palaeobiological aspects, the teeth of Octodontotherium , as well as those of Orophodon , reflect an unspecialized herbivorous diet as suggested by Kalthoff & Green (2018), which contradicts the myrmecophagous ancestral condition in sloths suggested by Gaudin & Croft (2015). Furthermore, Octodontotherium is graviportal and plantigrade, whereas Similhapalops is more agile and perhaps arboreal, as is Hapalops (Toledo 2016).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…A recent study [43] comparing tooth microwear patterns using stereomicroscopy and scanning electron microscopy (SEM) showed that the combination of the two approaches leads to a more robust and objective interpretation of feeding adaptations, especially in extinct taxa. Here, we applied a different combination of methods to analyze microwear (stereomicroscopy and 3D surface texture) for a sample of ten tritylodontid taxa spanning the Upper Triassic to Lower Cretaceous.…”
Section: Methodsmentioning
confidence: 99%